Young stroke due to vascular anomaly from neurofibromatosis type 1. (21st September 2012) - Krishnaswami, Vachagan; Gilmore, James; Vahidassr, Djamil
Abstract : Aetiology of stroke in young is often different to that of an older person. In nearly half of these cases no cause is established. Every effort should be explored to establish a cause as treatment varies accordingly and the prognosis with rehabilitation is favourable when compared with older people. We present a case of pontine infarct in a 43-year-old man due to vascular ectasia associated with neurofibromatosis type 1. Following the stroke, the patient went through intensive rehabilitation where he had a good functional outcome.